Particulate phases are key in controlling dissolved iron concentrations in the (sub)tropical North Atlantic. Issue 5 (4th March 2017) - Milne, Angela; Schlosser, Christian; Wake, Bronwyn D.; Achterberg, Eric P.; Chance, Rosie; Baker, Alex R.; Forryan, Alex; Lohan, Maeve C.
Abstract: The supply and bioavailability of iron (Fe) controls primary productivity and N2 fixation in large parts of the global ocean. An important, yet poorly quantified, source to the ocean is particulate Fe (pFe). Here we present the first combined dataset of particulate, labile‐particulate (L‐pFe), and dissolved Fe (dFe) from the (sub)tropical North Atlantic. We show a strong relationship between L‐pFe and dFe, indicating a dynamic equilibrium between these two phases whereby particles "buffer" dFe and maintain the elevated concentrations observed. Moreover, L‐pFe can increase the overall "available" (L‐pFe + dFe) Fe pool by up to 55%. The lateral shelf flux of this available Fe was similar in magnitude to observed soluble aerosol‐Fe deposition, a comparison that has not been previously considered. These findings demonstrate that L‐pFe is integral to Fe cycling and hence plays a role in regulating carbon cycling, warranting its inclusion in Fe budgets and biogeochemical models. Key Points: Labile‐particulate iron has a key role in iron cycling and can increase the overall "available" iron pool by up to 55% in the OMZ A strong relationship between particles and dissolved iron indicates that L‐pFe "buffers" the elevated dFe concentrations observed Lateral shelf transport of available Fe (L‐pFe + dFe) supplied a similar magnitude of iron as atmospheric sources